Digital transformation in higher education. Part a : best practices and challenges - Lytras, Miltiadis D.; Serban, Andreea Claudia; Alkhaldi, Afnan; Malik, Sawsan; Aldosemani, Tahani (Emerald Publishing Limited, 2024)
Digital Transformation in Higher Education is a pivotal reference through the transformative power of emerging technologies in academia. Addressing the dual nature of technology as both a challenge and an opportunity, this book presents a rich overview of strategies for integrating digital technology-driven advancements. From chatbots enhancing adult learning to AI ethics and micro-credentials, it illuminates a future where digital transformation is key for the unique value proposition of higher education. Each chapter offers actionable insights and case studies, setting the stage for educators and leaders to harness digital technology's potential and lead with innovation.
Keywords: Transformative learning.; Educational innovations.; Education, Higher -- Technological innovations.; Education -- Computers & Technology.; Higher education, tertiary education.; Educational equipment and technology, computer-aided learning (CAL); elektronické knihy; electronic books